Akibat Hukum Ketidakpastian Hukum Batas Waktu Deferred Prosecution Agreement (Dpa) Pada Sistem Peradilan Pidana Indonesia - Nadif Maulana; Daffa Alfan Kaukaba Bintang; Fathiya Nur Rosyida; Mochamad Lucky Ibnu Chaliki (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The Deferred Prosecution Agreement (DPA) regulation in Article 328 of Law No. 20 of 2025 concerning the Criminal Procedure Code (KUHAP) is an alternative resolution for corporate crimes. However, the lack of a time limit for Public Prosecutors and Judges in reviewing the DPA requests creates a legal obstacles. This normative research concludes that the lack of a time limit violates the principles of legality and legal certainty. The implications are triggering arbitrary law enforcement, corporate status registration, the threat of bankruptcy and mass layoffs. As an operational solution, it is recommended that implementing regulations (PP/PERMA/PERJA) be immediately established that set a maximum time limit, optimize law enforcement oversight instruments and develop transparent DPA eligibility indicators to ensure legal certainty.